A laboratory study on sediment resuspension within arrays of rigid cylinders. (June 2016) - Tinoco, Rafael O.; Coco, Giovanni
Highlights: Dense arrays of rigid cylinders enhance sediment resuspension. Resuspension thresholds can be characterized by a modified Shields parameter. Physical and biological effects must be considered in resuspension studies. Abstract: We present results from laboratory experiments on flow through submerged arrays of rigid cylinders embedded in a sandy bed. Using rigid, cylindrical elements to mimic vegetation and benthos, we account for only the physical effects resulting from their presence, eliminating biological factors, such as biofilms and root systems. In line with previous findings, rigid arrays modify the flow mean and turbulent velocity statistics. However, even if the flow speed is significantly damped within dense arrays, the amount of sediment that gets lifted into suspension increases as the density of the array increases due to array– and cylinder-scale turbulence. We present a first attempt to provide predictive relationships of suspended sediment concentration using an alternative approach for the Shields parameter with an empirical coefficient to account for turbulence generated by submerged arrays of rigid cylinders. A similar analysis, using a ratio of populated to non-populated Shields parameter, is conducted to predict resuspension as a function of array density.